Social Media Tools at Developing Academic Writing Skills - Charan, Aftab Ahmed; Buriro, Ghulam Ali (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
Facebook is considered as an effective Computer Mediated Communication (CMC) form. It is estimated that 2/3rd majority of Pakistani Facebook users are below 24 years old. The users spent around 40 minutes every day on facebook. They are either reading posts or responding by different emojis or comments. The study attempts to weigh the role of Facebook in developing writing skills in the students of English literature. 210 students of literature from four public sector universities participated in this research. A 15 item questionnaire suing a 5 – pint Likert scale was applied to record their observations. All students were invited to write at least one academic paragraph. Later their views, draft and profiles were cross tabulated through a data base to determine the results. The results show that 87% students use Facebook. The users consider Facebook as an opportunity to improve their writing skills. Among those who do not use Facebook around 30% did not participate in paragraph writing. The communication traffic on Facebook is found pertinent, critical and relevant. It was established that Facebook and other social media channels can be useful of distant or e-learning prospects.